Active chatter suppression for milling process with sliding mode control and electromagnetic actuator. (February 2020) - Wan, Shaoke; Li, Xiaohu; Su, Wenjun; Yuan, Junpeng; Hong, Jun
Highlights: An active milling system with electromagnetic actuator is modeled. An active sliding mode controller is designed for the chatter suppression. A spindle system integrated with electromagnetic actuator is developed for the active chatter suppression. Abstract: Milling chatter is a major factor limiting the machining efficiency and imposing poor surface finishes and machine tool damage, which is highly needed to be suppressed in the machining process. In order to control the unwanted chatter vibration, this research presents active milling chatter suppression using sliding mode control and electromagnetic actuator. The model of active milling chatter control system, with the electromagnetic actuator being considered, is presented firstly. In addition, the steady states caused by static milling force are neglected in the presented model. Then, an active sliding mode controller is designed, in which a dynamic output feedback sliding surface is introduced and the velocity state is not needed in the closed-loop system. The time delay item in the model are considered as disturbance, which makes the controller design easier. Simulation results show that the chatter-free domain is significantly improved in a wide spindle speed range. Milling experiments are also performed on a designed spindle system integrated with electromagnetic actuator, and the experimental results illustrate that the milling chatter can be well suppressed with the presented method and system, which shows advantages of robustness and practicality.